Hong Kong's Academic Advantage - Altbach, Philip; Postiglione, Gerard (International Higher Education, 2012)
Hong Kong's top universities have achieved considerable success in the rankings and are recognized for their quality. This article examines the reasons for Hong Kong's success, and compares Hong Kong with mainland China. Among the themes discussed are good governance, internationalization, high academic salaries, and others.